Preparation method and application of in-situ curing polymer electrolyte for lithium-sulfur battery

Through the use of in-situ curing technology and nitrate additives, the problem of poor contact between the electrode and the electrolyte interface in the solid battery and the difficulty of transmission of the electrolyte interface in the solid battery realizes the high-discharge ratio and high-cycle stability of solid-state lithium-sulfur batteries.

CN119381546APending Publication Date: 2025-01-28CENT SOUTH UNIV

Patent Information

Application Number
CN202411568213.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The capacity and cyclic properties of solid-state batteries in actual work are still hugely different from those of liquid ion batteries. This is mainly due to the fixed shape of the solid-state electrolyte and the inability to immerse the electrode surface and pores, resulting in poor interface contact and difficulty in ion transmission.

Method used

The in -situ curing technology is used to prepare polymer electrolytes, and nitrate additives are added to the electrolyte to form a high -ion -based nitrogen -rich interface layer of the lithium negative surface, which inhibits the growth of lithium branches, improves the battery's reaction dynamics and active substances Utilization rate.

Benefits of technology

Effectively inhibit the shuttle shuttle, reduce the interface resistance between the electrode and the electrolyte, improve the capacity of ion transmission, and improve the battery's high discharge ratio capacity and high cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381546A_ABST
    Figure CN119381546A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an in-situ curing polymer electrolyte for a lithium-sulfur battery, and belongs to the technical field of solid-state batteries, the preparation method comprises the following steps: stirring and mixing an initiator, a polymeric monomer, a lithium salt and an additive to obtain a uniform precursor solution; and 2, dropwise adding the precursor solution obtained in the step 1 to the surface of a diaphragm, and carrying out thermal initiation polymerization to obtain the polymer electrolyte. According to the preparation method and application of the in-situ curing polymer electrolyte for the lithium-sulfur battery, through an in-situ curing process, shuttling of polysulfide is inhibited, the interface resistance between an electrode and the electrolyte is reduced, and the ion transmission capacity is improved; the nitrate ester additive is added into the electrolyte, so that a nitrogen-rich stable interface layer with high ionic conductivity is formed on the surface of the lithium negative electrode under the condition that the polymerization state of the electrolyte is not damaged, the growth of lithium dendrites is effectively inhibited, and the assembled solid polymer lithium-sulfur battery keeps excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a preparation method and application of an in-situ solidified polymer electrolyte for lithium-sulfur batteries. Background Art

[0002] Solid electrolytes have excellent mechanical properties, flame retardancy, and no leakage. They can effectively inhibit the growth of lithium dendrites, improve battery safety, and reduce the requirements for battery packaging status and monitoring circuits. In addition, solid electrolytes can effectively avoid the generation of polysulfides in lithium-sulfur batteries and inhibit the shuttle effect. Due to these advantages, research on solid electrolytes has shown a rapid growth trend in recent years. However, solid electrolytes have a fixed morphology and cannot infiltrate the electrode surface and pores, resulting in poor interface contact and difficulty in ion transmission. The performance of solid-state batteries in actual work, such as capacity and cyclability, is still far behind that of liquid ion batteries.

[0003] At present, solid electrolyte systems include sulfides, halides, oxides, polymers, etc. Oxide solid electrolytes have extremely high ionic conductivity, but the preparation process is complicated and the interface resistance is high; halide solid electrolytes have high ionic conductivity, good deformability and a wide electrochemical window, but they still face challenges in electrode compatibility, high voltage stability and preparation process; sulfide electrolytes have high ionic conductivity and excellent ductility, but poor chemical stability and environmental stability, and high cost; in contrast, polymer solid electrolytes have excellent flexibility and processability, and are more compatible with existing liquid battery production processes and have received widespread attention, but polymer solid electrolytes have the problem of low room temperature ionic conductivity. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of an in-situ solidified polymer electrolyte for a lithium-sulfur battery. Through the in-situ solidification process, polysulfide shuttling is inhibited, the interface resistance between the electrode and the electrolyte is reduced, and the ion transmission capacity is improved. By adding nitrate additives to the electrolyte, a nitrogen-rich stable interface layer with high ion conductivity is formed on the surface of the lithium negative electrode without destroying the polymer state of the electrolyte, the growth of lithium dendrites is effectively inhibited, and the assembled solid polymer lithium-sulfur battery maintains excellent performance.

[0005] To achieve the above object, the present invention provides a method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery, comprising the following steps: Step 1: Stir and mix the initiator, polymerization monomer, lithium salt and additive to obtain a uniform precursor solution; Step 2: Add the precursor solution obtained in step 1 dropwise onto the surface of the diaphragm, and obtain a polymer electrolyte through thermal initiation polymerization.

[0006] Preferably, in step 1, the mass fraction of the initiator is 0.8-5‰, the mass fraction of the polymerization monomer is 30-60%, the mass fraction of the additive is 1-10%, and the mass fraction of the lithium salt is 30-60%.

[0007] Preferably, the initiator in step 1 is one or more of aluminum fluoride, boron trifluoride, boron pentafluoride, aluminum trifluoromethanesulfonate and tin fluoride.

[0008] Preferably, the polymerizable monomer is dioxolane, and the lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium hexafluorophosphate and lithium iodide.

[0009] Preferably, the additive is one of isosorbide dinitrate, amyl nitrate, isopropyl nitrate and triethylene glycol dinitrate.

[0010] Preferably, the stirring time in step 1 is 0.2-2h.

[0011] Preferably, the heating temperature of the thermally initiated polymerization in step 2 is 40-70° C., and the heating time is 10-20 h.

[0012] The present invention provides an application of an in-situ solidified polymer electrolyte for a lithium-sulfur battery. The polymer electrolyte prepared by the above-mentioned preparation method of an in-situ solidified polymer electrolyte for a lithium-sulfur battery is applied to a solid-state lithium-sulfur battery.

[0013] Preferably, the preparation of the solid-state lithium-sulfur battery comprises the following steps: S1. Cut the positive electrode into a circular positive electrode sheet with a diameter of 10-15 mm and place it in the center of the positive electrode shell; S2, drip 10-50 μL of the precursor solution on the surface of the positive electrode sheet, then put in a polypropylene film, drip 10-50 μL of the precursor solution again, place the negative electrode sheet and encapsulate the battery; S3. The packaged battery is heat-treated, and the precursor solution and the polypropylene film are heat-treated to form a polymer electrolyte, thereby obtaining a solid-state lithium-sulfur battery, and the electrochemical performance thereof is tested.

[0014] Preferably, the positive electrode is one of a sulfur / carbon nanotube positive electrode, a sulfurized polyacrylonitrile positive electrode and a sulfur / ordered mesoporous carbon positive electrode; the negative electrode is one of a lithium metal negative electrode, a lithium boron alloy negative electrode and a lithium indium alloy.

[0015] Therefore, the present invention adopts the above-mentioned preparation method of the in-situ solidified polymer electrolyte for lithium-sulfur batteries and its application, which has the following beneficial effects: (1) The present invention adopts in-situ solidification technology to better solve the problem of poor interface contact between the electrode and the solid electrolyte, improve the interface ion conduction, and inhibit the shuttling problem faced by polysulfides in the liquid electrolyte, thereby improving the reaction kinetics and active material utilization of the battery, which is conducive to achieving a battery with high discharge specific capacity and high cycle stability.

[0016] (2) The present invention does not change the traditional battery preparation process and is simple to operate, making it suitable for large-scale production of this type of solid-state battery.

[0017] (3) The present invention solves the problem of incompatibility between lithium nitrate and solid electrolytes by introducing organic nitrate additives, effectively adjusts the composition and morphology of the SEI film on the lithium surface, protects lithium metal from the influence of interfacial side reactions, improves the cycle stability of the battery, increases the room temperature ionic conductivity of the polymer electrolyte, and improves the reaction kinetics of the battery.

[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a method for preparing an in-situ solidified polymer electrolyte for lithium-sulfur batteries of the present invention and application example 1, comparative example 1, and a solidification visualization diagram of the polymer solid electrolyte obtained in comparative example 2; Figure 2 The present invention is a method for preparing an in-situ solidified polymer electrolyte for lithium-sulfur batteries and its application. The hydrogen element nuclear magnetic spectrum of the polymer solid electrolyte obtained in Example 1 and Comparative Example 1; Figure 3 The present invention is a method for preparing an in-situ solidified polymer electrolyte for lithium-sulfur batteries and its application. Example 1 and Comparative Example 1 show the carbon element nuclear magnetic spectrum of the polymer solid electrolyte obtained; Figure 4 The present invention is a method for preparing an in-situ solidified polymer electrolyte for lithium-sulfur batteries and the lithium-lithium symmetric impedance diagram of the polymer solid electrolyte obtained in Examples 1-3 and Comparative Examples 1-2; Figure 5 This is a cycle performance diagram of a solid-state lithium-sulfur battery obtained in Example 1 of a method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery of the present invention and its application; Figure 6 This is a cycle performance diagram of a solid-state lithium-sulfur battery obtained in Example 1 of the present invention according to a method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery and its application; Figure 7 This is a preparation method of an in-situ solidified polymer electrolyte for a lithium-sulfur battery of the present invention and a cycle performance diagram of a solid-state lithium-sulfur battery obtained in comparative example 2 of its application. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0021] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0022] The present invention provides a method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery, comprising the following steps: Step 1: Stir and mix the initiator, polymerization monomer, lithium salt and additive for 0.2-2h to obtain a uniform precursor solution; the mass fraction of the initiator is 0.8-5‰, the mass fraction of the polymerization monomer is 30-60%, the mass fraction of the additive is 1-10%, and the mass fraction of the lithium salt is 30-60%.

[0023] The initiator is one or more of aluminum fluoride, boron trifluoride, boron pentafluoride, aluminum trifluoromethanesulfonate and tin fluoride. The polymerizable monomer is dioxolane, and the lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium hexafluorophosphate and lithium iodide. The additive is one of isosorbide nitrate, amyl nitrate, isopropyl nitrate and triethylene glycol dinitrate.

[0024] Step 2: dripping the precursor solution obtained in step 1 onto the surface of the diaphragm, and obtaining a polymer electrolyte through thermally initiated polymerization, wherein the heating temperature of the thermally initiated polymerization is 40-70° C., and the heating time is 10-20 hours.

[0025] The present invention provides an application of an in-situ solidified polymer electrolyte for a lithium-sulfur battery. The polymer electrolyte prepared by the above-mentioned preparation method of an in-situ solidified polymer electrolyte for a lithium-sulfur battery is applied to a solid-state lithium-sulfur battery.

[0026] The preparation of solid-state lithium-sulfur batteries includes the following steps: S1. Cut the positive electrode into a circular positive electrode sheet with a diameter of 10-15 mm and place it in the center of the positive electrode shell; S2, drip 10-50 μL of the precursor solution on the surface of the positive electrode sheet, then put in a polypropylene film, drip 10-50 μL of the precursor solution again, place the negative electrode sheet and encapsulate the battery; S3. The packaged battery is heat-treated, and the precursor solution and the polypropylene film are heat-treated to form a polymer electrolyte, thereby obtaining a solid-state lithium-sulfur battery, and the electrochemical performance thereof is tested.

[0027] The positive electrode is one of a sulfur / carbon nanotube positive electrode, a sulfurized polyacrylonitrile positive electrode and a sulfur / ordered mesoporous carbon positive electrode; the negative electrode is one of a lithium metal negative electrode, a lithium-boron alloy negative electrode and a lithium-indium alloy.

[0028] Example 1 The present invention provides a method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery, comprising the following steps: In the anhydrous and oxygen-free atmosphere of the glove box, 0.57 g of lithium bis(trifluoromethylsulfonyl)imide was dispersed in a mixed solution of 1 mL of dioxolane and 0.04 mL of isosorbide nitrate, and stirred at 500 r / min for 60 min to obtain a uniformly distributed solution. 0.19 mg of aluminum trifluoromethanesulfonate and 0.007 mg of aluminum fluoride were added to the mixed solution, and stirred at 500 r / min for 15 min to obtain a polymer precursor solution. The precursor solution was poured into a 2 mL glass bottle, placed on a heating table, and heated at 40 ° C for 12 h to obtain a poly-DOL solid electrolyte, which was tested and observed.

[0029] The preparation of the in-situ solidified lithium-lithium symmetric battery comprises the following steps: In the water-free and oxygen-free atmosphere of the glove box, the prepared polymer precursor solution was used as the battery electrolyte, the polypropylene film was used as the diaphragm, and the metal lithium sheet was used as the positive and negative electrodes to assemble a lithium-lithium symmetrical battery. The electrolyte drop amounts on both sides of the diaphragm were 20 μL on the positive electrode side and 20 μL on the negative electrode side, respectively. The assembled battery was placed on a heating table and heated at 40°C for 12 hours to obtain a polymer solid-state lithium-lithium symmetrical battery. The impedance performance was tested using the CHI760e electrochemical workstation. The final ionic conductivity was calculated using the formula σ=L / (SR). Where σ is the conductivity, in units of S / cm, L is the average thickness of the polymer solid electrolyte membrane, in units of cm; S is the area of ​​the polymer solid electrolyte membrane, in units of cm 2 ; R is the body impedance of the polymer solid electrolyte membrane, in Ω.

[0030] The preparation of in-situ cured polymer lithium-sulfur battery includes the following steps: Sublimated sulfur and carbon nanotubes were mixed in a mass ratio of 6:4, and the mixed powder was ball-milled for 2 hours and then put into an ampoule and sealed. In an argon atmosphere, the sulfur / carbon nanotube positive electrode was obtained by heating at 155°C for 12 hours. The sulfur / carbon nanotube composite material, acetylene black and PVDF material (mass ratio 7:2:1) were mixed, and after sufficient grinding, an appropriate amount of NMP solution was added and stirred for 6 hours to form a uniform slurry. The above slurry was coated on the surface of aluminum foil, dried in a vacuum oven at 50°C for 24 hours, and then cut into circular positive electrode sheets with a diameter of 12 mm for use; In the water-free and oxygen-free atmosphere of the glove box, the prepared sulfur / carbon nanotube positive electrode was placed in the positive electrode shell, the prepared polymer precursor solution was used as the battery electrolyte, the polypropylene film was used as the diaphragm, and the metal lithium sheet was used as the negative electrode to assemble a lithium-sulfur battery. The amount of electrolyte added on both sides of the diaphragm was 20 μL on the positive electrode side and 20 μL on the negative electrode side, respectively. The assembled battery was placed on a heating table and heated at 40°C for 12 h to obtain a polymer solid-state lithium-sulfur battery for electrochemical performance testing.

[0031] Figure 5 The cycle performance diagram of the in-situ cured polymer lithium-sulfur battery prepared in Example 1 at room temperature and a discharge rate of 0.2C. It can be seen from the figure that the battery has a first-cycle discharge capacity of 842mAh / g and a charge capacity of 875mAh / g. After 190 cycles, the discharge capacity is 455mAh / g, the charge capacity is 461mAh / g, and the discharge capacity retention rate is 54%. The high discharge capacity and capacity retention rate of the battery are related to the introduction of organic nitric acid-based additives, which effectively regulate the composition and morphology of the SEI film on the electrode surface, inhibit the occurrence of side reactions at the electrode electrolyte interface, and hinder the shuttling of polysulfides.

[0032] Example 2 The present invention provides a method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery, comprising the following steps: In the anhydrous and oxygen-free atmosphere of the glove box, 1.15 g of lithium bis(trifluoromethylsulfonyl)imide was dispersed in a mixed solution of 1 mL of dioxolane and 0.08 mL of isosorbide nitrate, and stirred at 500 r / min for 60 min to obtain a uniformly distributed solution. 0.19 mg of aluminum trifluoromethanesulfonate and 0.007 mg of aluminum fluoride were added to the mixed solution, and stirred at 500 r / min for 15 min to obtain a polymer precursor solution. The precursor solution was poured into a 2 mL glass bottle, placed on a heating table, and heated at 70 ° C for 10 h to obtain a poly-DOL solid electrolyte.

[0033] The preparation of the in-situ solidified lithium-lithium symmetric battery comprises the following steps: In the anhydrous and oxygen-free atmosphere of the glove box, the prepared polymer precursor solution was used as the battery electrolyte, the polypropylene film was used as the diaphragm, and the metal lithium sheet was used as the positive and negative electrodes to assemble a lithium-lithium symmetric battery. The electrolyte drop amount on both sides of the diaphragm was 20μL on the positive electrode side and 20μL on the negative electrode side. The assembled battery was placed on a heating table and heated at 70℃ for 10h to obtain a polymer solid-state lithium-lithium symmetric battery. The impedance test was performed on it.

[0034] Example 3 The present invention provides a method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery, comprising the following steps: In the anhydrous and oxygen-free atmosphere of the glove box, 1.72 g of lithium bis(trifluoromethylsulfonyl)imide was dispersed in a mixed solution of 1 mL of dioxolane and 0.1 mL of isosorbide nitrate, and stirred at 500 r / min for 60 min to obtain a uniformly distributed solution. 0.38 mg of aluminum trifluoromethanesulfonate and 0.014 mg of aluminum fluoride were added to the mixed solution, and stirred at 500 r / min for 15 min to obtain a polymer precursor solution. The precursor solution was poured into a 2 mL glass bottle, placed on a heating table, and heated at 40 ° C for 12 h to obtain a poly-DOL solid electrolyte.

[0035] The preparation process of the in-situ solidified lithium-lithium symmetric battery is the same as that in Example 1.

[0036] Comparative Example 1 The operation of Comparative Example 1 is the same as that of Example 1, except for the type of additive, and specifically comprises the following steps: In the anhydrous and oxygen-free atmosphere of the glove box, lithium bis(trifluoromethylsulfonyl)imide and 16 mg of lithium nitrate were dispersed in a dioxolane solution. After stirring evenly, the initiator was added to the mixed solution to obtain a polymer precursor solution. The precursor solution was poured into a 2 mL glass bottle, placed on a heating table, and heated at 40 ° C for 12 h to obtain a poly-DOL solid electrolyte, which was then tested and observed.

[0037] Figure 6 The figure is a cycle performance diagram of the in-situ cured polymer lithium-sulfur battery prepared in Comparative Example 1 at room temperature under a discharge rate of 0.2C. It can be seen from the figure that the battery has a first cycle discharge capacity of 738mAh / g and a charge capacity of 831mAh / g. After 190 cycles, the discharge capacity is 229mAh / g, the charge capacity is 271mAh / g, and the discharge capacity retention rate is 31%. Compared with Example 1, the charge and discharge capacity difference of the battery in Comparative Example 1 is slightly increased, indicating that after the introduction of lithium nitrate, the electrolyte and electrode interface side reactions are effectively suppressed, but the battery capacity retention rate is still low, which is related to the shuttling of polysulfides in the liquid electrolyte.

[0038] Comparative Example 2 The operation of Comparative Example 2 is the same as that of Example 1, except that no additive is added in Comparative Example 2, and specifically comprises the following steps: In the anhydrous and oxygen-free atmosphere of the glove box, lithium bis(trifluoromethylsulfonyl)imide was dispersed in a dioxolane solution and stirred evenly. Then, an initiator was added to the mixed solution to obtain a polymer precursor solution. The precursor solution was poured into a 2 mL glass bottle, placed on a heating table, and heated at 40 ° C for 12 h to obtain a poly-DOL solid electrolyte, which was then tested and observed.

[0039] Figure 7The figure is a cycle performance diagram of the in-situ cured polymer lithium-sulfur battery prepared in comparative example 2 at room temperature and a discharge rate of 0.2C. It can be seen from the figure that the battery has a discharge capacity of 720mAh / g and a charge capacity of 1072mAh / g in the first cycle. After 190 cycles, the discharge capacity is 195mAh / g, the charge capacity is 260mAh / g, and the discharge capacity retention rate is 27%. Compared with Example 1, the charge capacity of the battery is much higher than the discharge capacity, indicating that a serious side reaction occurs at the interface between the electrolyte and the electrode, indicating that the nitric acid group plays an important role in regulating the composition and morphology of the SEI film on the electrode surface, inhibiting the occurrence of side reactions at the electrode electrolyte interface, and hindering the shuttling of polysulfides.

[0040] Comparative Example 3 The operation of Comparative Example 3 is the same as that of Example 1, except for the concentration of the initiator, and specifically comprises the following steps: In the anhydrous and oxygen-free atmosphere of the glove box, lithium bis(trifluoromethylsulfonyl)imide was dispersed in a mixed solution of dioxolane and isosorbide nitrate, 1 mg of aluminum trifluoromethanesulfonate and 0.028 mg of aluminum fluoride were added to the mixed solution to obtain a polymer precursor solution, the precursor solution was poured into a 2 mL glass bottle, placed on a heating table, and heated at 40°C for 12 hours to obtain a poly-DOL solid electrolyte, which was tested and observed, and it was found that at this concentration, the electrolyte exploded at room temperature to form large particles, and battery assembly and performance testing could not be performed. The present invention found that the initiator concentration should be controlled below 5%, otherwise the polymer electrolyte for lithium-sulfur batteries cannot be synthesized.

[0041] Figure 1 The solidification visualization diagrams of the polymer solid electrolytes obtained in Example 1, Comparative Example 1, and Comparative Example 2 show that the polymer solid electrolyte prepared in Example 1 is in a transparent solid state, without large solid particles, and does not flow after inversion. After the electrolyte in Comparative Example 1 is inverted, it flows downward and does not polymerize successfully. Although the electrolyte in Comparative Example 2 is polymerized into a solid state, the polymerization is uneven, and the liquid-solid coexistence interface can be clearly seen, indicating that the introduction of additives can adjust the curing reaction rate, avoid speed runaway, and trigger implosion.

[0042] Figure 2The hydrogen element nuclear magnetic spectra of the polymer solid electrolyte obtained in Example 1 and Comparative Example 1. According to literature and theoretical research, the chemical shifts of 3.78ppm and 4.78ppm in the hydrogen nuclear magnetic spectrum correspond to -CH2-CH2-O- and -CH2-O-CH2- on the cyclic ether monomer, respectively. After polymerization, the above chemical shifts move to 3.61ppm and 4.64ppm, respectively, corresponding to -O-CH2-CH2-O- and -O-CH2-O-. From the figure, we can see that the hydrogen nuclear magnetic spectrum of the polymer solid electrolyte prepared in Example 1 is mainly poly-DOL, containing a small amount of monomers, indicating the successful preparation of the solid polymer electrolyte.

[0043] Figure 3 The carbon NMR spectra of the polymer solid electrolyte obtained in Example 1 and Comparative Example 1 are shown in Figure 1. According to literature and theoretical research, the chemical shifts of 94.82ppm and 64.3ppm in the carbon NMR spectra correspond to -CH2-CH2-O- and -CH2-O-CH2- on the cyclic ether monomers, respectively. After polymerization, the carbon chemical shifts assigned to the main chain shift from 94.82ppm to 95.4ppm and from 64.3ppm to 66.7ppm, respectively. From the figure, we can see that the carbon NMR spectrum of the polymer solid electrolyte prepared in Example 1 is mainly poly-DOL and contains a small amount of monomers, indicating the successful preparation of the solid polymer electrolyte.

[0044] Figure 2 and Figure 3 The hydrogen element nuclear magnetic resonance spectrum and carbon element spectrum of the polymer solid electrolyte prepared in Comparative Example 1 show that the electrolyte is mainly composed of DOL and contains a small amount of poly-DOL. The strong interaction between lithium nitrate and the monomer hinders the polymerization of the monomer and cannot achieve the purpose of forming a polymer electrolyte, indicating that the type of nitrate plays an important role in the present invention.

[0045] Figure 4 The lithium-lithium symmetric impedance diagrams of the polymer solid electrolytes obtained in Examples 1-3 and Comparative Examples 1-2 are obtained. The ionic conductivity of the polymer solid electrolyte is calculated by the formula. The ionic conductivity of Example 1 is 0.91 mS / cm, which is close to the ionic conductivity of conventional liquid electrolytes, indicating that the present invention successfully prepares a polymer solid electrolyte with high ionic conductivity.

[0046] The ionic conductivity of the polymer solid electrolyte was calculated by the formula. The ionic conductivity of Comparative Example 1 was 0.75 mS / cm, slightly lower than that of Example 1, indicating that the type of additives can affect the ionic conductivity of the solid electrolyte.

[0047] The ionic conductivity of the polymer solid electrolyte of Comparative Example 2 was calculated by the formula. The ionic conductivity of Comparative Example 2 was 0.38 mS / cm, which was much lower than that of Example 1, indicating that organic nitrate additives play an important role in improving the ionic conductivity of polymer electrolytes.

[0048] Therefore, the present invention adopts the above-mentioned preparation method of the in-situ solidified polymer electrolyte for lithium-sulfur batteries and its application, and suppresses the shuttling of polysulfide through the in-situ solidification process, reduces the interface resistance between the electrode and the electrolyte, and improves the ion transmission capacity; by adding nitrate additives to the electrolyte, a nitrogen-rich stable interface layer with high ion conductivity is formed on the surface of the lithium negative electrode without destroying the polymerization state of the electrolyte, effectively suppressing the growth of lithium dendrites, so that the assembled solid polymer lithium-sulfur battery maintains excellent performance.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery, characterized in that: The following steps are involved: Step 1: Stir and mix the initiator, polymerization monomer, lithium salt and additive to obtain a uniform precursor solution; Step 2: Add the precursor solution obtained in step 1 dropwise onto the surface of the diaphragm, and obtain a polymer electrolyte through thermal initiation polymerization.

2. The method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery according to claim 1, characterized in that: In step 1, the mass fraction of the initiator is 0.8-5‰, the mass fraction of the polymerization monomer is 30-60%, the mass fraction of the additive is 1-10%, and the mass fraction of the lithium salt is 30-60%.

3. The method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery according to claim 2, characterized in that: The initiator in step 1 is one or more of aluminum fluoride, boron trifluoride, boron pentafluoride, aluminum trifluoromethanesulfonate and tin fluoride.

4. The method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery according to claim 3, characterized in that: The polymerizable monomer is dioxolane, and the lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium hexafluorophosphate and lithium iodide.

5. The method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery according to claim 4, characterized in that: The additive is one of isosorbide dinitrate, amyl nitrate, isopropyl nitrate and triethylene glycol dinitrate.

6. The method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery according to claim 5, characterized in that: The stirring time in step 1 is 0.2-2h.

7. The method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery according to claim 6, characterized in that: The heating temperature of the thermally initiated polymerization in step 2 is 40-70° C., and the heating time is 10-20 hours.

8. An application of an in-situ solidified polymer electrolyte for lithium-sulfur batteries, characterized in that: The polymer electrolyte prepared by the method for preparing an in-situ solidified polymer electrolyte for a lithium-sulfur battery as described in claim 7 is applied to a solid-state lithium-sulfur battery.

9. The use of an in-situ solidified polymer electrolyte for lithium-sulfur batteries according to claim 8, characterized in that: The preparation of solid-state lithium-sulfur batteries includes the following steps: S1. Cut the positive electrode into a circular positive electrode sheet with a diameter of 10-15 mm and place it in the center of the positive electrode shell; S2, drip 10-50 μL of the precursor solution on the surface of the positive electrode sheet, then put in a polypropylene film, drip 10-50 μL of the precursor solution again, place the negative electrode sheet and encapsulate the battery; S3. The packaged battery is heat-treated, and the precursor solution and the polypropylene film are heat-treated to form a polymer electrolyte, thereby obtaining a solid-state lithium-sulfur battery, and the electrochemical performance thereof is tested.

10. The use of an in-situ solidified polymer electrolyte for lithium-sulfur batteries according to claim 9, characterized in that: The positive electrode is one of a sulfur / carbon nanotube positive electrode, a sulfurized polyacrylonitrile positive electrode and a sulfur / ordered mesoporous carbon positive electrode; the negative electrode is one of a lithium metal negative electrode, a lithium-boron alloy negative electrode and a lithium-indium alloy.

Citation Information

Patent Citations

  • Lithium-sulfur battery electrolyte, lithium-sulfur battery and activation method of lithium-sulfur battery

    CN114678591A

  • Polymer electrolyte and preparation method and application thereof

    CN115249838A

  • Nitrate additives for nonaqueous electrolyte rechargeable cells

    US6136477A

Cited By

  • Molybdenum disulfide / polyether-based in-situ composite solid electrolyte as well as preparation method and application thereof

    CN120048986A

  • Molybdenum disulfide / polyether-based in-situ composite solid electrolyte, preparation method and application thereof

    CN120048986B